Method for determination of optical purity of 2-arylpropanoic acids using urea derivatives based on a 1,1'-binaphthalene skeleton as chiral NMR solvating agents: Advantages and limitations thereof - Cuřínová, Petra; Hájek, Peter; Janků, Kristýna; Holakovský, Roman (Chirality, 2019)
Five optically active urea derivatives (1-5) were used as NMR solvating agents for analysis of the optical purity of different 2-arylpropanoic acids commonly used as nonsteroidal anti-inflammatory drugs. These novel chiral solvating agents were more efficient at discriminating the respective enantiomers of targets than the chiral solvating agents known so far, without the need to add a base for achieving the signal splitting. The advantages and limits of the use of these novel chiral solvating agents were studied.
Keywords: chiral solvating agent; nonsteroidal anti-inflammatory drugs; arylpropanoic acids; binaphthalene; urea